Intrinsic factors associated with return to sport after anterior cruciate ligament reconstruction: A systematic review - Cheryl A. Ross; Amanda Clifford; Quinette A. Louw (AOSIS, 2015)
Objectives: The anterior cruciate ligament is the most commonly injured ligament in the knee, with an average of only 64% of affected athletes returning to their pre-injury level of sport. Intrinsic factors associated with an increased likelihood of return to sport may be addressed during rehabilitation to improve the outcome of the reconstruction. The objectives of this review were to systematically appraise publications from six electronic databases describing intrinsic factors that may be associated with return to sport after anterior cruciate ligament reconstruction. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Methodological quality appraisal was performed according to the Critical Appraisal Skills Programme for cohort studies. We performed a descriptive synthesis of the findings that associated intrinsic factors with return to sport. Results: Ten studies were included in the review. The findings show that fear of re-injury is a common reason for not returning to participation in sport. Younger patients may be more likely to return to sport, but findings regarding gender were equivocal, with male competitive athletes appearing to be more likely to return to sport than their female counterparts. Good knee function is not always associated with a higher likelihood to return to sport. Conclusion: Fear of re-injury and age should be considered in the management of sports participants after anterior cruciate ligament reconstruction.